Professional self-awareness and medical record data integrity: A phenomenological study among health information management personnel in indonesian primary care - Nurfazirah Nurfazirah; Muh Ihsan Kamaruddin; Jessy Andre Mangaya Takke (Journal Interdisciplinary Health, 2026)
Introduction: Accurate and consistent medical record data are essential for patient safety, continuity of care, service evaluation, and health-system decision-making. However, data-quality problems may persist despite electronic medical record implementation because documentation is also shaped by human behaviour and organisational conditions. This study aimed to explore how health information management personnel understand and practise professional self-awareness, its perceived role in maintaining medical record accuracy and consistency, and the conditions supporting or constraining reflective data-management practices in Indonesian primary care. Research Methodology: A descriptive phenomenological study was conducted at Antang Primary Health Centre, Makassar, Indonesia, from April to June 2026. Twelve health information management personnel were recruited through purposive sampling. Data were collected through semi-structured in-depth interviews, non-participant observation, field notes, and document review. Interview data were transcribed verbatim and analysed using a phenomenological thematic procedure involving significant-statement identification, meaning-unit formulation, coding, categorisation, and theme development. Trustworthiness was supported through triangulation, member checking, peer debriefing, reflexive journaling, and an audit trail. Results: Five major themes and ten subthemes were identified: professional responsibility for data integrity, reflective verification of medical record data, recognition and correction of documentation errors, organisational barriers to consistent documentation, and development of a collective data-quality culture. Participants had 1–12 years of professional experience, and interviews lasted 35–60 minutes. High workload, time pressure, incomplete documentation, and inconsistent recording practices constrained reflective verification. Conclusion: Professional self-awareness supports medical record integrity through verification, error recognition, reflection, communication, and corrective action. Primary healthcare facilities should combine individual accountability with standardised checklists, routine audits, supportive supervision, non-punitive error reporting, and digital validation mechanisms